A "Business Researcher" View on Opportunities for Psychology in Entrepreneurship Research. Issue 3 (8th May 2016) - Davidsson, Per
Abstract : In this short essay I offer some "business researcher" advice on how to leverage a strong background in psychology when attempting to contribute to the maturing field of "entrepreneurship research". Psychologists can benefit from within‐discipline research, e.g. on emergence, small groups, fit, and expertise as well as method strengths in, e.g. experimentation, operationalisation of constructs, and multi‐level modelling. However, achieving full leverage of these strengths requires a clear conceptualisation of "entrepreneurship" as well as insights into the challenges posed by the nature of this class of phenomena.